Efficient key management for publish/subscribe system in cloud scenarios. (2016) - Cui, Zongmin; Gao, Guangyong; Zhou, Caixue; Yu, Jing; Deng, Anyuan; Deng, Changshou
Publish/subscribe system has been well-studied for many applications. However, the key management of existing methods is not efficient enough. Therefore, we propose an efficient key management scheme based on dichotomy derivation for publish/subscribe system in cloud scenarios. The scheme derives a subscription interval to two dichotomy subscription intervals. Thus, the key management costs are logarithmic growth in base 2 with the length of subscription interval. Comparing with the linear growth of existing methods, our scheme is much more efficient for big data in cloud scenarios. Experimental results show that our scheme significantly outperforms existing methods in key management.